Respuesta :
The answer is A.) 2x+2y+6
Because when you distribute you multiply the term outside of the parenthesis individually with everything inside the parenthesis. So, it should look like this:
2(x+y+3)=2(x)+2(y)+2(3)=2x+2y=6
Hope this helps :)
Because when you distribute you multiply the term outside of the parenthesis individually with everything inside the parenthesis. So, it should look like this:
2(x+y+3)=2(x)+2(y)+2(3)=2x+2y=6
Hope this helps :)
The correct answer is A because 2 distributed to x so x equals 1 it is still 2 but take away the x so it is 2x do the same for y= 2y and then 2x3 = 6 so 2x+2y+6